ECOS DO MOVIMENTO DA NEGRITUDE NAS LITERATURAS AFRICANAS DE LÍNGUA PORTUGUESA - Vanessa Ribeiro Teixeira (TRF2, 2017)
The thirties of twentieth century were marked by the emergence of the Negritude Movement, articulated by black students, inside and outside Africa, who proposed to rethink the place and value of black culture in the world, through a critical writing of a social, philosophical and political nature. Responsible for the publication of the journals Légitime Défense (1932), L'Étudiant Noir (1934) e Présence Africaine (1947-1968), these thinkers "intend to be united by the affirmation of the black culture, to the black's awareness of his own condition" (SANTILLI, 1985, p. 174). Among the many researchers of African Portuguese-language Literature, it is important to consider the impact of the new ways of looking at the historical development and the cultural significance of the black population, in Africa and in the diaspora, which culminated in the French-speaking Negritude Movement and its rereading, about the construction of an authentically African literature in the Portuguese colonies. The poetry, especially, from the late of the fortieths of twentieth century, claims the possibility of bringing to its center both the drama of colonized black people and the valorization of their culture.